Loyalty in halal tourism: The roles of sharia-compliant service quality, Islamic experience, and religiosity - Sukma, Andhi; Oktaviani, Desy; Latifah, Ifa (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2026)
Purpose – This study examines how Sharia-Compliant Service Quality (SCSQ) and Islamic Experience (IE) shape Muslim tourist loyalty in halal tourism through Trust (TR), Perceived Value (PV), and Satisfaction (SAT).Design/methodology/approach – Survey data were collected from Muslim tourists who had visited Lombok and experienced halal tourism services. The final cleaned sample respondents. The data were analyzed using PLS-SEM, including measurement model assessment, discriminant validity checks, bootstrapping, mediation testing, moderation analysis, control-variable analysis, and Importance–Performance Map Analysis (IPMA).Findings – The refined model shows that SCSQ significantly enhances IE, and IE significantly strengthens TR, PV, and SAT. However, TR, PV, SAT, IE, and SCSQ do not directly translate into Tourist Loyalty. The proposed indirect effects of IE on Tourist Loyalty through TR, PV, and SAT are also not supported. Religiosity negatively moderates the relationship between SCSQ and IEits moderating effect on the relationship between IE and Tourist Loyalty is not significant at the 5% level. These findings indicate that positive halal service and experiential evaluations may be necessary but insufficient to generate loyalty in a halal tourism destination.Research limitations/implications – The cross-sectional and single-destination design limits causal inference and generalisability. Future research should use longitudinal and multi-destination designs to compare halal tourism contexts with different levels of destination maturity and examine more loyalty mechanisms.Practical implications – Halal tourism managers should move beyond technical compliance by creating authentic, credible, emotionally meaningful, and differentiated Islamic tourism experiences that strengthen tourists’ confidence, perceived value, and destination relevance.Originality/value – This study refines halal tourism loyalty research by showing Sharia-compliant service quality enhances Islamic experience and internal evaluations. However, these mechanisms alone tourist loyalty.